Justice and Security Provision in Post-War Mozambique – A Politically Contested Field. (January 2014) - Kyed, Helene Maria
<x content-type="archive" xml:space="preserve">Abstract</x> This article explores the complex empirical landscape of justice and security provision in post-war Mozambique, and its political dynamics. It scrutinises the formal policy framework, which today recognises legal pluralism. The current legislation not only fails to fully recognise the de facto role played by non-state providers, but also to acknowledge the various layers of informal interaction and competition that in practice occur between these and official state institutions. There are political reasons for this. Justice and security provision constitute a minefield of power interests and overlapping claims to authority, which have deep historical roots. State officials and the national government fear losing power if non-state actors are given clear rights and mandates. Unclear legislation also eases political instrumentalisation by politicians and power-holders. The risk is that justice and security provision becomes more about politics than about problem solving and access to justice.